MicroRNA in cardiovascular calcification: Focus on targets and extracellular vesicle delivery mechanisms - Goettsch, Claudia (2013)
Cardiovascular calcification is a prominent feature of chronic inflammatory disorders — such as chronic kidney disease (CKD), type 2 diabetes (T2D), and atherosclerosis — that associate with significant morbidity and mortality. The concept that similar pathways control both bone remodeling and vascular calcification is widely accepted, but the precise mechanisms of calcification remain largely unknown. The central role of microRNAs (miRNA) as fine-tune regulators in the cardiovascular system and bone biology has gained acceptance and has raised the possibility for novel therapeutic targets. Additionally, circulating miRNAs have been proposed as biomarkers for a wide range of cardiovascular diseases, but knowledge of miRNA biology in cardiovascular calcification is very limited. This review focuses on the role of miRNA in cardiovascular disease, with emphasis on osteogenic processes. Herein, we discuss the current understanding of miRNAs in cardiovascular calcification. Furthermore, we identify a set of miRNAs common to diseases associated with cardiovascular calcification (CKD, T2D, and atherosclerosis), and we hypothesize that these miRNAs may provide a molecular signature for calcification. Finally, we discuss this novel hypothesis with emphasis on known biological and pathological osteogenic processes (e.g. osteogenic differentiation, release of calcifying matrix vesicles). The aim of this review is to provide an organized discussion of the known links between miRNA and calcification that provide emerging concepts for future studies on miRNA biology in cardiovascular calcification, which will be critical for developing new therapeutic strategies.